Numerical methods for the high speed solution of integral equations in wireless communications - O'Nuallain, Eamonn Pol (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2001)
This thesis investigates the the appropriateness of integral equations for use in determining electric field coverage over sub-urban terrain which is illuminated by an arbitrarily placed transmitter. Sub-urban terrain is the term used to describe undulating terrain with an homogeneous or piecewise homogeneous distribution of clutter (vegetation, buildings, rocks etc.). The exact numerical solution for electric field coverage is given in the form of coupled integral equations.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin